10.3726/978-3-0353-0745-0/25 (Inactive DOIs, 2016)
The prevalence of malaria parasite species in parts of Africa is rapidly changing and influenced by detection methods. These trends could be influenced by differential vector competence/capacity of anophelines for Plasmodium species, but these factors have been well described only for P. falciparum (Pf) and are unclear in the context of mixed and non-falciparum infections. During two clinical trials testing ivermectin for malaria control in the same region of Burkina Faso in 2015 and 2019-2020, we sampled participants' blood and Anopheles spp. mosquitoes from their households and tested these samples for Plasmodium species. Plasmodium prevalence in participants' blood was high in both trials (samples with Pf monoinfections: 1st trial: 42% [95% CI: 34-49%]; 2nd trial: 40% [35-45%]). Although Pf monoinfections comprised most infections in the first trial, mixed and non-falciparum infections comprised 27% of infections in the second trial. An. gambiae s.l. were the most abundant mosquitoes captured during the trials, but An. funestus was prevalent in the second trial, and parasite species prevalence differed in abdominal and head-and-thorax tissues of these two vector species. Most notably, Pf sporozoites were significantly more prevalent than other parasite species in An. gambiae s.l. (Pf 66% [56% to 74%] versus P. ovale (Po)/P. malariae (Pm) 34% [26% to 44%]), whereas Po sporozoites were detected more than other parasite species in An. funestus (P. ovale 63% [46% to 78%] versus Pf/Pm 37% [22% to 54%]). Our data suggest potential differential vector competence or vectorial capacities for Plasmodium species at the study site, which may significantly impact malaria epidemiology, disease prevalence, and disease control efforts.